Fuel cell anode gas diffusion electrode with low mass transfer resistance to co and method of making

By using a microporous layer-free design and an inner and outer double-layer catalytic layer structure for the fuel cell anode gas diffusion electrode, the problem of high mass transfer polarization loss under high CO content was solved, achieving efficient gas and proton transport, and improving the performance and CO resistance of the fuel cell.

CN116646532BActive Publication Date: 2026-11-06SHANGHAI INST OF SPACE POWER SOURCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310697395.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2026-11-06
Estimated Expiration
2043-06-13

AI Technical Summary

Technical Problem

Under reformed gas feed with high CO content and low hydrogen concentration, proton exchange membrane fuel cells suffer from high anode activation polarization and mass transfer polarization losses, resulting in low performance and short lifespan. Existing methods also present system complexity and safety issues.

Method used

The gas diffusion layer design without microporous layer is adopted, combined with the inner and outer double-layer catalytic layer structure. The outer catalytic layer contains CO-resistant catalyst, and the inner and outer catalytic layers have gradient pores and gradient binder distribution, which constructs a double catalytic layer anode with gradient porosity and binder distribution, thereby improving CO resistance and reducing mass transfer resistance.

Benefits of technology

It effectively reduces mass transfer resistance, shortens the performance difference of fuel cells with reformed gas feed and pure hydrogen feed, increases electrochemical active area, improves CO resistance, and simplifies system structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116646532B_ABST
    Figure CN116646532B_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing a CO-resistant, low-mass-transfer-resistance anode gas diffusion electrode for fuel cells, comprising: preparing a diffusion layer; coating an outer catalyst layer slurry onto the surface of the diffusion layer to obtain an outer catalyst layer; the outer catalyst layer slurry comprising a CO-resistant platinum-based catalyst, a binder, and a pore-forming agent; coating an inner catalyst layer slurry onto the surface of the outer catalyst layer to obtain an inner catalyst layer; the inner catalyst layer slurry comprising a platinum-based catalyst, a binder, and a pore-forming agent; the porosity of the outer catalyst layer is greater than that of the inner catalyst layer, and the average pore size of the outer catalyst layer is greater than that of the inner catalyst layer. This invention also discloses an anode gas diffusion electrode obtained by the above preparation method. This invention can effectively reduce mass transfer resistance and shorten the performance difference of fuel cells with reformed gas feed and pure hydrogen feed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of proton exchange membrane fuel cell technology, and specifically relates to a fuel cell anode gas diffusion electrode with low CO mass transfer resistance and its preparation method. Background Technology

[0002] Proton exchange membrane fuel cells (PEMFCs) are considered promising next-generation power sources due to their advantages such as high energy conversion efficiency, high power density, zero pollutant emissions, and relatively simple design. Among them, the HT-PEMFC, operating at 160-180℃, has attracted widespread attention due to its relatively strong impurity tolerance, faster electrode reaction kinetics, and simple hydrothermal management, showing broad application prospects in portable power supplies, combined heat and power (CHP), stationary power plants, and auxiliary power sources. However, when fed with reformed gas (CO≥3%, H2≤50%) with high CO content and low hydrogen concentration, compared to pure hydrogen feed, HT-PEMFCs exhibit higher anode activation polarization and mass transfer polarization losses at high current densities, resulting in lower performance and shorter lifespan.

[0003] To address the above issues, current solutions mainly include anode oxygen injection, reformer pretreatment, and the use of CO-resistant catalysts. Anode oxygen injection involves adding a small amount of oxidant, such as oxygen, to the fuel to oxidize and remove CO, reducing anode activation polarization losses. However, direct mixing of the oxidant and fuel leads to reduced fuel utilization and raises system safety concerns. Reformer pretreatment uses catalytic reactors such as carbon monoxide-water conversion and selective oxidation to reduce CO concentration to below 10 ppm. However, this method requires additional processes and energy, making the system relatively complex. CO-resistant catalysts are Pt-based, incorporating other substances to lower the oxidation potential of CO. The most widely used CO-resistant catalysts reduce the oxidation potential of CO through the synergistic effect of Pt and Ru, significantly reducing cell activation polarization in the presence of CO. However, their effect on reducing mass transfer polarization losses at low hydrogen concentrations is not significant. Summary of the Invention

[0004] The purpose of this invention is to overcome the above-mentioned defects and provide a fuel cell anode gas diffusion electrode with low CO resistance and a method for its preparation. This invention solves the technical problem of high mass transfer polarization loss in traditional anode gas diffusion electrodes. This invention can effectively reduce mass transfer resistance and shorten the performance difference of fuel cells under reformed gas feed and pure hydrogen feed.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0006] In the anode gas diffusion electrode of this invention, the gas diffusion layer only includes a support layer. The gas diffusion layer design without micropores can shorten the gas diffusion distance, enhance gas transport, and significantly reduce the transport resistance of hydrogen under reformed gas feed. The catalyst layer in the anode gas diffusion electrode has an inner and outer double-layer structure. By controlling the types of catalysts in the inner and outer catalyst layers, especially the use of CO-resistant catalysts in the outer anode catalyst layer and the distribution of pores and binders in the inner and outer catalyst layers, a double-catalyst layer anode with gradient pores and gradient binder distribution is constructed. This is beneficial for the synergistic construction of gas transport channels and proton transport channels, increasing the electrochemical active area, which can significantly improve CO resistance and reduce mass transfer resistance, thereby achieving the effective construction of a fuel cell anode gas diffusion electrode with low CO resistance and mass transfer resistance.

[0007] A method for fabricating a fuel cell anode gas diffusion electrode with low CO mass transfer resistance, comprising:

[0008] Preparation of diffusion layer;

[0009] An outer catalyst layer slurry is coated onto the surface of the diffusion layer to obtain the outer catalyst layer; the outer catalyst layer slurry includes a CO-resistant platinum-based catalyst, a binder, and a pore-forming agent.

[0010] An inner catalyst layer slurry is coated onto the surface of the outer catalyst layer to obtain the inner catalyst layer; the inner catalyst layer slurry includes a platinum-based catalyst, a binder, and a pore-forming agent.

[0011] The porosity of the outer catalyst layer is greater than that of the inner catalyst layer, and the average pore size of the outer catalyst layer is greater than that of the inner catalyst layer.

[0012] Furthermore, the diffusion layer includes a support layer;

[0013] Methods for preparing the diffusion layer include:

[0014] Carbon paper, carbon cloth, carbon felt, titanium mesh, or stainless steel mesh are immersed in an aqueous PTFE solution.

[0015] The impregnated paper, carbon cloth, carbon felt, titanium mesh or stainless steel mesh are heat-treated to obtain a diffusion layer;

[0016] The mass percentage of PTFE in the diffusion layer is 5%–35%.

[0017] Furthermore, the impregnated paper, carbon cloth, carbon felt, titanium mesh, or stainless steel mesh are subjected to heat treatment at 340–360°C for 0.1–2 hours.

[0018] Furthermore, the CO-resistant platinum-based catalyst in the outer catalyst layer slurry includes one or more of PtRu / C, PtSn / C, PtBi / C, or PtRh / C;

[0019] The platinum-based catalyst in the inner catalyst layer slurry includes one or more of Pt black or Pt / C.

[0020] Furthermore, the outer catalyst layer slurry and the binder in the outer catalyst layer slurry include one or more of PTFE, PVDF, FEP, mPBI, ABPBI, or PFA;

[0021] The pore-forming agent in the outer catalyst layer slurry includes one or more of ammonium bicarbonate, ammonium oxalate, ammonium nitrate, or ammonium sulfate.

[0022] Furthermore, the preparation method of the outer catalyst layer slurry includes:

[0023] The anti-CO platinum-based catalyst was uniformly dispersed in a solvent to obtain the first catalyst slurry;

[0024] Prepare an aqueous adhesive solution, add a pore-forming agent to the aqueous adhesive solution, and disperse evenly to obtain a homogeneous and transparent first solution; the mass percentage of adhesive in the aqueous adhesive solution is 0.5% to 10%, and the mass ratio of adhesive to pore-forming agent in the first solution is 1 / 10 to 10 / 1;

[0025] The first solution is dropped into the first catalyst slurry and dispersed evenly to obtain the outer catalyst layer slurry. In the outer catalyst layer slurry, the mass of the pore-forming agent is 10% to 20% of the total mass of the anti-CO platinum-based catalyst, binder and pore-forming agent.

[0026] Furthermore, the preparation method of the inner catalyst layer slurry includes:

[0027] The platinum-based catalyst was uniformly dispersed in a solvent to obtain a second catalyst slurry;

[0028] Prepare an aqueous adhesive solution, add a pore-forming agent to the aqueous adhesive solution, and disperse it evenly to obtain a homogeneous and transparent second solution; the mass percentage of ionomer in the aqueous adhesive solution is 0.5-10%, and the mass ratio of adhesive to pore-forming agent in the second solution is 1 / 10-10 / 1;

[0029] The second solution is added dropwise into the second catalyst slurry and dispersed evenly to obtain the inner catalyst layer slurry. In the inner catalyst layer slurry, the mass of the pore-forming agent is 5% to 10% of the total mass of the platinum-based catalyst, binder, and pore-forming agent.

[0030] Furthermore, the method of coating the diffusion layer surface with an external catalyst layer slurry includes ultrasonic spraying, screen printing or slit direct coating. After coating the diffusion layer surface with the external catalyst layer slurry, the obtained product is placed in a muffle furnace and calcined at 300℃~400℃ for 0.5h~2h to obtain the external catalyst layer.

[0031] Methods for coating the outer catalyst layer surface with an inner catalyst layer slurry include ultrasonic spraying, screen printing, or slit coating. After coating the outer catalyst layer surface with the inner catalyst layer slurry, the resulting product is placed in a muffle furnace and calcined at 300℃~400℃ for 0.5h~2h to obtain the inner catalyst layer.

[0032] Furthermore, in the obtained outer catalyst layer, the mass percentage of the pore-forming agent is 10% to 20%; in the obtained inner catalyst layer, the mass percentage of the pore-forming agent is 5% to 10%.

[0033] In both the outer catalyst layer and the inner catalyst layer, the mass percentage of the binder is 10%-40%, and the mass percentage of the binder in the outer catalyst layer is greater than that in the inner catalyst layer.

[0034] The catalyst loading in both the outer and inner catalyst layers is 0.05–0.5 mg / cm³. 2 Furthermore, the catalyst loading in the outer catalyst layer is higher than that in the inner catalyst layer.

[0035] A fuel cell anode gas diffusion electrode with low CO mass transfer resistance is obtained by the above-mentioned method for preparing a fuel cell anode gas diffusion electrode with low CO mass transfer resistance, and includes a diffusion layer, an outer catalyst layer and an inner catalyst layer.

[0036] The porosity of the outer catalyst layer is 40%–50%, and the average pore size is 0.5–5 μm;

[0037] The porosity of the inner catalyst layer is 20%–30%, and the average pore size is 0.05–1 μm.

[0038] Compared with the prior art, the present invention has at least one of the following advantages:

[0039] (1) The present invention provides a diffusion layer without microporous layer, which can significantly reduce the transmission resistance of hydrogen under reforming gas feed;

[0040] (2) The present invention uses a CO-resistant catalyst, which can significantly improve the CO resistance;

[0041] (3) This invention can significantly improve CO resistance by screening and adding dual-catalytic anode catalysts and designing gradient pore distribution, while reducing mass transfer resistance and shortening the performance difference of fuel cells under reformed gas feed and pure hydrogen feed. Attached Figure Description

[0042] Figure 1 This is a schematic diagram of the fuel cell anode gas diffusion electrode with low CO mass transfer resistance according to the present invention.

[0043] Figure 2 This is a SEM image of the membrane electrode structure in Embodiment 1 of the present invention;

[0044] Figure 3 The figures show the membrane electrode polarization characteristic curves of different anode gas diffusion electrode structures in the embodiments and comparative examples of the present invention; in the figures, a represents the membrane electrode structure of embodiment 1, b represents the membrane electrode structure of comparative example 2, and c represents the membrane electrode structure of comparative example 1. Detailed Implementation

[0045] The features and advantages of the present invention will become clearer and more apparent from the following detailed description.

[0046] The term “exemplary” as used herein means “serving as an example, embodiment, or illustration.” Any embodiment illustrated herein as “exemplary” is not necessarily to be construed as superior to or better than other embodiments. Although various aspects of embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless specifically indicated otherwise.

[0047] This invention provides a CO-resistant fuel cell anode gas diffusion electrode with low mass transfer resistance and its preparation method. Compared with traditional anode gas diffusion electrodes, the design without a microporous layer can significantly reduce the hydrogen transport resistance under reformed gas feed. On the other hand, the screening and addition of CO-resistant catalysts in the dual-catalytic anode, as well as the design of gradient pores and gradient binder distribution, can significantly improve the CO resistance, while reducing mass transfer resistance and shortening the performance difference between reformed gas feed and pure hydrogen feed.

[0048] This invention provides a fuel cell anode gas diffusion electrode with low CO mass transfer resistance:

[0049] The anode gas diffusion electrode includes a diffusion layer, an outer catalyst layer, and an inner catalyst layer. The diffusion layer only contains a support layer and no longer contains a microporous layer. The outer catalyst layer contains an electrocatalyst with strong CO resistance. The porosity and average pore size of the outer catalyst layer are larger than those of the inner catalyst layer.

[0050] In one specific embodiment, the diffusion layer only includes a support layer and does not include a microporous layer. The support layer is carbon paper, carbon cloth, carbon felt, titanium mesh or stainless steel mesh impregnated with PTFE aqueous solution, wherein the PTFE content is 10%-40%.

[0051] In one specific embodiment, the porosity of the outer catalyst layer of the anode is 40%-50%, and the porosity of the inner catalyst layer of the anode is 20%-30%, with the porosity of the outer catalyst layer being higher than that of the inner catalyst layer;

[0052] In one specific embodiment, the loading of the noble metal platinum in the outer catalyst layer of the anode is 0.05-0.5 mg / cm³. 2 The loading of platinum in the inner catalyst layer of the anode is 0.05-0.5 mg / cm³. 2 The noble metal loading of the outer catalyst layer of the anode is higher than that of the inner catalyst layer.

[0053] In one specific embodiment, the binder content in the outer catalyst layer of the anode is 10%-40%, and the binder content in the inner catalyst layer of the anode is 10%-40%. The binder content in the outer catalyst layer is higher than that in the inner catalyst layer. The higher distribution of binder in the outer layer is beneficial for the uniform distribution of phosphoric acid, effectively constructing the three-phase interface and improving the utilization rate of the catalyst.

[0054] This invention also provides a method for preparing the above-mentioned fuel cell anode gas diffusion electrode with low CO mass transfer resistance:

[0055] S1: First, carbon paper, carbon cloth, carbon felt, titanium mesh or stainless steel mesh are immersed in PTFE aqueous solution to obtain a gas diffusion layer that does not contain a microporous layer.

[0056] S2: The catalyst slurry containing anti-CO catalyst, pore-forming agent and binder is dispersed evenly by stirring, ultrasonication and homogenization, and then evenly coated on the gas diffusion layer by scraping, spraying and screen printing. The loading, thickness and porosity of noble metal in the catalyst layer are controlled, and then it is placed on a hot table to dry.

[0057] S3: The catalyst slurry containing platinum-based catalyst, pore-forming agent and binder in the inner catalyst layer of the anode is dispersed evenly by stirring, ultrasonication and homogenization, and then uniformly coated on the outer catalyst layer of the anode by scraping, spraying, screen printing and other methods. The loading, thickness and porosity of noble metal in the catalyst layer are controlled, and then it is placed on a hot table to dry, thereby obtaining a fuel cell anode gas diffusion electrode with low CO mass transfer resistance.

[0058] In one specific embodiment, in step S1, the diffusion layer consists only of a support layer. The support layer is made by immersing carbon cloth or carbon paper in a 1%-20% PTFE emulsion for approximately 10-100 seconds, and then removing it to calculate the percentage of PTFE impregnation. This impregnation and drying process is repeated until the PTFE loading of the support layer is 5-35 wt.%. Finally, the hydrophobic carbon cloth or carbon paper is placed in a muffle furnace and heat-treated at 340-360°C for 0.1-2 hours, then cooled to room temperature and removed. The support layer can also be carbon felt, titanium mesh, or stainless steel mesh impregnated with a PTFE aqueous solution, wherein the PTFE content is 5%-35 wt.%.

[0059] In one specific embodiment, in step S2, the outer catalyst layer of the dual-catalyst layer anode includes a CO-resistant noble metal platinum-based catalyst, a binder, and a pore-forming agent.

[0060] 1) The preparation process of the catalyst slurry for the outer catalyst layer is as follows:

[0061] a) Disperse 5%-50% (mass percentage) of the CO-resistant platinum-based catalyst in isopropanol / water solution, and circulate it by ultrasonication and stirring 2-3 times, each time for 0.1-1h, to ensure uniform dispersion, and obtain catalyst slurry ①; isopropanol / water solution refers to a mixed solution of isopropanol and water; the CO-resistant platinum-based catalyst is one of PtRu / C, PtSn / C, PtBi / C or PtRh / C;

[0062] b) Use any one or more of PTFE, PVDF, FEP, mPBI, ABPBI, and PFA as binders, and ammonium bicarbonate, ammonium oxalate, ammonium nitrate, and ammonium sulfate as pore-forming agents. Weigh out 0.5wt%-10wt% of the binder aqueous solution, add a certain amount of pore-forming agent, control the mass ratio of binder to pore-forming agent to be between 1 / 10 and 10 / 1, and sonicate and stir to disperse it evenly to obtain a uniform and transparent solution ②.

[0063] c) According to the mass ratio of pore-forming agent in the catalyst layer being between 10% and 20%, take out a certain amount of solution ②, slowly drip it into solution ①, and sonicate and stir for 2-3 cycles, each time for 0.1-1 hours to disperse it evenly and obtain catalyst slurry ③;

[0064] 2) The catalyst slurry ③ is coated onto the diffusion layer using techniques such as ultrasonic spraying, screen printing, and slot coating. Then, it is placed in a muffle furnace and calcined at 300℃-400℃ for 0.5h-2h to obtain the outer catalyst layer. The loading of the noble metal catalyst in the outer catalyst layer is 0.05-0.5 mg / cm³. 2 The binder content is 10%-40%, the porosity is 40%-50%, and the average pore size is between 0.5-5μm;

[0065] In one specific embodiment, in step S3, the inner catalyst layer of the dual-catalyst anode includes a platinum-based catalyst, a binder, and a pore-forming agent.

[0066] 1) The preparation process of the catalyst slurry for the inner catalyst layer is as follows:

[0067] a) Disperse the platinum-based catalyst in an isopropanol / water solution, and circulate it by ultrasonication and stirring 2-3 times, each time for 0.1-1h, to ensure uniform dispersion, thereby obtaining catalyst slurry ④; the platinum-based catalyst is Pt black or Pt / C;

[0068] b) Using PTFE or PVDF as a binder, and ammonium bicarbonate, ammonium oxalate, ammonium nitrate, ammonium sulfate, etc. as pore-forming agents, weigh 0.5wt%-10wt% of PTFE or PVDF aqueous solution, add a certain amount of pore-forming agent, control the mass ratio of PTFE or PVDF to pore-forming agent to be between 1 / 10 and 10 / 1, and sonicate and stir to disperse it evenly to obtain a uniform and transparent solution⑤;

[0069] c) According to the mass ratio of pore-forming agent in the catalyst layer between 5% and 10%, take out a certain amount of solution ⑤, slowly drip it into solution ④, and sonicate and stir for 2-3 cycles, each time for 0.1-1h to disperse it evenly to obtain catalyst slurry ⑥;

[0070] 2) The catalyst slurry ⑥ is coated onto the outer catalyst layer using techniques such as ultrasonic spraying, screen printing, and slot coating. Then, it is placed in a muffle furnace and calcined at 300℃-400℃ for 0.5h-2h to obtain the inner catalyst layer. The loading of the noble metal catalyst in the inner catalyst layer is 0.05-0.5 mg / cm³. 2 The binder content is 10%-40% (the binder content in the outer catalyst layer is greater than that in the inner catalyst layer), the porosity is 20%-30%, and the average pore size is between 0.05-1μm.

[0071] Compared with existing technologies, the CO-resistant and low-mass-transfer-resistance fuel cell anode gas diffusion electrode of the present invention, on the one hand, adopts a gas diffusion layer design without microporous layers, which can shorten the gas diffusion distance and significantly reduce the hydrogen transport resistance under reformed gas feed; on the other hand, the CO-resistant catalyst and the gradient pore and gradient binder distribution design of the outer catalyst layer of the dual-catalyst anode are conducive to the synergistic construction of gas transport channels and proton transport channels, increasing the electrochemical active area, which can significantly improve the CO resistance, reduce mass transfer resistance, shorten the performance difference under reformed gas feed and pure hydrogen feed, and realize the application of CO-resistant and low-mass-transfer-resistance fuel cell anode gas diffusion electrode.

[0072] Example 1

[0073] See Figure 1 A fuel cell anode gas diffusion electrode with low CO mass transfer resistance includes a diffusion layer 1, an outer catalyst layer 2, and an inner catalyst layer 3. After hydrogen, carbon monoxide, and reformed gases such as carbon dioxide are uniformly dispersed through the diffusion layer, hydrogen and carbon monoxide first undergo electrochemical oxidation reactions in the outer catalyst layer, and unreacted hydrogen and carbon monoxide diffuse into the inner catalyst layer to continue participating in the reaction.

[0074] The method for fabricating a fuel cell membrane electrode assembly with a CO-resistant, low-mass-transfer-resistance anode gas diffusion electrode is as follows:

[0075] Preparation of the anolyte gas diffusion layer: Carbon paper was treated with a 2 wt.% PTFE emulsion. First, the commercial carbon paper was weighed, then immersed in the PTFE emulsion for approximately 30 seconds, removed, dried with a hairdryer, and weighed again. The percentage of PTFE immersed was then calculated. This impregnation and drying process was repeated until the PTFE loading of the support layer reached 20 wt.%. Finally, the hydrophobic carbon paper was placed in a muffle furnace and heat-treated at 340°C for 0.5 hours. After cooling to room temperature, the anolyte gas diffusion layer without micropores was obtained.

[0076] Preparation of the outer catalyst layer of the anode: 20% wt. PtRu / C catalyst was dispersed in isopropanol / water solution, magnetically stirred, and ultrasonically circulated 3 times for 20 min each time to ensure uniform dispersion, resulting in catalyst slurry ①; PTFE was used as a binder and ammonium bicarbonate as a pore-forming agent. 2 wt% PTFE aqueous solution was weighed, and a certain amount of pore-forming agent was added, controlling the mass ratio of PTFE to pore-forming agent to be 1:1. The solution was ultrasonically stirred to ensure uniform dispersion, resulting in a homogeneous and transparent solution ②; A certain amount of solution ② was taken out according to the pore-forming agent accounting for 20% of the mass of the catalyst layer, and slowly dripped into solution ①. The solution was magnetically stirred, ultrasonically circulated, and circulated 3 times for 20 min each time to ensure uniform dispersion, resulting in catalyst slurry ③; The catalyst slurry ③ was coated onto the anode gas diffusion layer using ultrasonic spraying technology, controlling the loading of noble metal Pt in the outer catalyst layer to be 0.3 mg / cm³. 2 The PTFE content is 20%, the porosity is 50%, and the average pore size is between 0.5 and 5 μm. Then, it is placed in a muffle furnace and calcined at 350 °C for 40 min to obtain the outer catalyst layer of the anode.

[0077] Preparation of the inner catalyst layer of the anode: 50% Pt / C catalyst was dispersed in isopropanol / water solution, magnetically stirred, and ultrasonically circulated three times for 20 minutes each time to ensure uniform dispersion, resulting in catalyst slurry ④; PTFE was used as a binder and ammonium bicarbonate as a pore-forming agent. 2 wt% PTFE aqueous solution was weighed, and a certain amount of pore-forming agent was added, controlling the mass ratio of PTFE to pore-forming agent to be 1:1. The solution was ultrasonically stirred to ensure uniform dispersion, resulting in a homogeneous and transparent solution ⑤; A certain amount of solution ② was taken out according to the pore-forming agent accounting for 10% of the mass of the catalyst layer, and slowly dripped into solution ①. The solution was magnetically stirred, ultrasonically circulated, and circulated three times for 20 minutes each time to ensure uniform dispersion, resulting in catalyst slurry ③; The catalyst slurry ③ was coated onto the anode diffusion layer using ultrasonic spraying technology, controlling the loading of noble metal Pt in the inner catalyst layer to be 0.2 mg / cm³. 2 The PTFE content is 10%, the porosity is 30%, and the average pore size is between 0.05 and 1 μm. Then, it is placed in a muffle furnace and calcined at 350°C for 40 min to obtain the anode gas diffusion electrode.

[0078] Preparation of the cathode gas diffusion electrode (cathode GDE): The gas diffusion layer in the cathode GDE uses commercially available Torray carbon paper containing a microporous layer. First, a 60% PtCo / C catalyst was dispersed in an isopropanol / water solution, magnetically stirred, and ultrasonically circulated three times for 20 minutes each time to ensure uniform dispersion, yielding catalyst slurry ①. Using PTFE as a binder, 60 wt% PTFE aqueous solution was diluted to a 2 wt% PTFE aqueous solution, ultrasonically stirred, and uniformly dispersed to obtain a homogeneous and transparent solution ②. A certain amount of solution ② was taken and slowly dripped into solution ①, magnetically stirred, ultrasonically circulated, and circulated three times for 20 minutes each time to ensure uniform dispersion, yielding catalyst slurry ③. The catalyst slurry ③ was coated onto the cathode gas diffusion layer using ultrasonic spraying technology, controlling the loading of noble metal Pt in the catalyst layer to be 0.8 mg / cm³. 2 The PTFE content is 10%, and then it is placed in a muffle furnace and calcined at 350℃ for 40 minutes to obtain a cathode gas diffusion electrode.

[0079] Preparation of the electrolyte membrane: A PBI / H3PO4 composite membrane was used as the electrolyte membrane and prepared by an impregnation method. First, commercially available mPBI membranes were cut to the required size. Then, the cut membranes were immersed in 85wt% phosphoric acid at 100°C for the appropriate time. Excess phosphoric acid on the membrane surface was blotted dry with filter paper, and the membrane was quickly weighed to obtain the phosphoric acid adsorption capacity. The phosphoric acid adsorption capacity (MPA / PBI) was assessed using the mass ratio of phosphoric acid to resin. The above acid immersion and weighing steps were repeated until the phosphoric acid adsorption capacity reached 370wt%.

[0080] The prepared anode gas diffusion electrode, cathode gas diffusion electrode, and electrolyte membrane are stacked in a mold in a specific order. Then, the membrane electrode is hot-pressed and formed in a hot press, and finally placed in a sealed bag for storage.

[0081] The above methods are used to obtain the fuel cell membrane electrode.

[0082] Comparative Example 1

[0083] Comparative Example 1 is a traditional membrane electrode with a microporous layer at the anode. The difference between it and Example 1 is that the anode gas diffusion electrode contains a microporous layer, while the catalyst layer is a single layer. The porosity, pore size, and PTFE content in the catalyst layer are uniformly distributed. No pore-forming agent is added to the anode catalyst layer, and it does not contain an anti-CO catalyst. The specific preparation process is as follows:

[0084] Preparation of the anode diffusion layer: The anode diffusion layer consists of an anode support layer and a microporous layer. Torray carbon paper was treated with a 2 wt.% PTFE emulsion. First, the commercial carbon paper was weighed, then immersed in the PTFE emulsion for approximately 30 seconds, removed, dried with a hairdryer, and weighed again to calculate the percentage of PTFE immersed. This impregnation and drying process was repeated until the PTFE loading of the support layer reached 20 wt.%. Finally, the hydrophobic carbon paper was placed in a muffle furnace and heat-treated at 350°C for 40 minutes. After cooling to room temperature, the anode support layer was obtained. Then, Vulcan XC-72 toner and the PTFE emulsion were mixed, and an appropriate amount of ethanol was added. The mixture was ultrasonically stirred to obtain a slurry, which was then screen-printed onto the surface of the anode support layer to form a microporous layer. The toner loading was fixed at 1 mg / cm³. 2 The PTFE content is 30%. It is placed in a muffle furnace and heat-treated at 350°C for 30 minutes. After cooling to room temperature, the anodic diffusion layer is obtained.

[0085] Preparation of the anolyte gas diffusion electrode: 20% Pt / C catalyst was dispersed in isopropanol / water solution, and the mixture was ultrasonically and stirred for 3 cycles, 0.15 h each time, to ensure uniform dispersion, resulting in catalyst slurry ①. 60% PTFEF was used as a binder, diluted with water, and ultrasonically and stirred to ensure uniform dispersion, resulting in a homogeneous and transparent 2wt% PTFE aqueous solution ②. A certain amount of solution ② was taken and slowly dripped into solution ①, and ultrasonically and stirred for 3 cycles, 0.2 h each time, to ensure uniform dispersion, resulting in catalyst slurry ③. The catalyst slurry ③ was coated onto the anolyte diffusion layer using ultrasonic spraying technology, and then calcined in a muffle furnace at 340℃ for 1 h, resulting in a noble metal catalyst loading of 0.5 mg / cm³ for the cathode catalyst layer. 2 The porosity is 20%, and the average pore size is between 0.05 and 1 μm.

[0086] Comparative Example 2

[0087] Comparative Example 2 is a membrane electrode with an anti-CO catalyst in the anode gas diffusion electrode. The difference from Example 1 is that the anode gas diffusion electrode contains a microporous layer, the catalyst layer is a single layer with uniform pores and PTFE content distribution, and no pore-forming agent is added to the anode catalyst layer, but an anti-CO catalyst is used. The specific preparation process is as follows:

[0088] Preparation of the anode diffusion layer: The anode diffusion layer consists of an anode support layer and a microporous layer. Torray carbon paper was treated with a 2 wt.% PTFE emulsion. First, the commercial carbon paper was weighed, then immersed in the PTFE emulsion for approximately 30 seconds, removed, dried with a hairdryer, and weighed again to calculate the percentage of PTFE immersed. This impregnation and drying process was repeated until the PTFE loading of the support layer reached 20 wt.%. Finally, the hydrophobic carbon paper was placed in a muffle furnace and heat-treated at 350°C for 40 minutes. After cooling to room temperature, the anode support layer was obtained. Then, Vulcan XC-72 toner and the PTFE emulsion were mixed, and an appropriate amount of ethanol was added. The mixture was ultrasonically stirred to obtain a slurry, which was then screen-printed onto the surface of the anode support layer to form a microporous layer. The toner loading was fixed at 1 mg / cm³. 2 The PTFE content is 30%. It is placed in a muffle furnace and heat-treated at 350°C for 30 minutes. After cooling to room temperature, the anodic diffusion layer is obtained.

[0089] Preparation of the anolyte gas diffusion electrode: 20% PtRu / C catalyst was dispersed in isopropanol / water solution, and the mixture was ultrasonically and stirred for 3 cycles, 0.15 h each time, to ensure uniform dispersion, resulting in catalyst slurry ①; 60% PTFE was used as a binder, diluted with water, and ultrasonically and stirred to ensure uniform dispersion, resulting in a homogeneous and transparent 2wt% PTFE aqueous solution ②; a certain amount of solution ② was taken out and slowly dripped into solution ①, and ultrasonically and stirred for 3 cycles, 0.2 h each time, to ensure uniform dispersion, resulting in catalyst slurry ③; the catalyst slurry ③ was coated onto the anolyte diffusion layer using ultrasonic spraying technology, and then placed in a muffle furnace and calcined at 340℃ for 1 h, resulting in a noble metal catalyst loading of 0.5 mg / cm³ for the cathode catalyst layer. 2 The porosity is 20%, and the average pore size is between 0.05 and 1 μm.

[0090] Performance testing

[0091] According to GB / T 20042.5-2009, the polarization curve of the obtained high-temperature proton exchange membrane fuel cell membrane electrode was tested. The specific operating conditions were: the single cell operating temperature was 180℃, the anode was fed with reformed gas (CO content of 3%, hydrogen concentration of 40%, and the remainder nitrogen), the cathode was fed with atmospheric pressure air, and the cathode / anode feed ratios were 3 / 1.3.

[0092] According to GB / T 20042.5-2009, the membrane electrode impedance of a high-temperature proton exchange membrane fuel cell was tested. The specific operating conditions were as follows: single cell operating temperature was 180℃, anode feed was reformed gas (CO content 3%, hydrogen concentration 40%, the remainder nitrogen), cathode feed was atmospheric pressure air, the cathode / anode feed ratio was 3 / 1.3, and the discharge current density was 0.5 A cm⁻¹.-2 .

[0093] The test results are attached. Figure 1-3 .

[0094] A schematic diagram of the double-layer anode gas diffusion electrode structure in Example 1 is shown below. Figure 1 As shown, the SEM image of the membrane electrode in Example 1 is as follows. Figure 2 As shown.

[0095] The performance test results of Example 1 and Comparative Examples 1 and 2 are shown in the figure. Figure 3 Under these conditions, it can be seen that the membrane electrode corresponding to Example 1 has higher performance at 0.1 A cm⁻¹. -2 The voltage can reach 690mV at 0.5A cm. -2 The voltage can reach 540mV. The performance of the membrane electrode corresponding to Comparative Example 2 and Comparative Example 1 is within 0.1A cm⁻¹. -2 The voltage can reach 600mV and 590mV at 0.5A cm. -2 The voltages reached only 420mV and 300mV. Compared with Comparative Examples 1 and 2, the membrane electrode of Example 1 showed better performance at low and medium-high current densities, indicating that the design of the absence of a microporous layer and the gradient pore and gradient binder distribution of the dual-catalytic anode are conducive to the synergistic construction of gas transport channels and proton transport channels, increasing the electrochemical active area, which can significantly improve the CO resistance and reduce the mass transfer resistance.

[0096] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.

[0097] The contents not described in detail in this specification are common knowledge to those skilled in the art.

Claims

1. A method for preparing a fuel cell anode gas diffusion electrode with low CO mass transfer resistance, characterized in that, include: Preparation of diffusion layer; An outer catalyst layer slurry is coated onto the surface of the diffusion layer to obtain the outer catalyst layer; The outer catalyst layer slurry includes a CO-resistant platinum-based catalyst, a binder, and a pore-forming agent; An inner catalyst layer slurry is coated onto the surface of the outer catalyst layer to obtain the inner catalyst layer; the inner catalyst layer slurry includes a platinum-based catalyst, a binder, and a pore-forming agent. The porosity of the outer catalyst layer is greater than that of the inner catalyst layer, and the average pore size of the outer catalyst layer is greater than that of the inner catalyst layer. The diffusion layer contains only the support layer; Methods for preparing the diffusion layer include: Carbon paper, carbon cloth, carbon felt, titanium mesh, or stainless steel mesh are immersed in an aqueous PTFE solution. The impregnated paper, carbon cloth, carbon felt, titanium mesh or stainless steel mesh are heat-treated to obtain a diffusion layer; The mass percentage of PTFE in the diffusion layer is 5-35%; The preparation methods of the external catalyst layer slurry include: The anti-CO platinum-based catalyst was uniformly dispersed in a solvent to obtain the first catalyst slurry; Prepare an aqueous adhesive solution, add a pore-forming agent to the aqueous adhesive solution, and disperse evenly to obtain a homogeneous and transparent first solution; the mass percentage of adhesive in the aqueous adhesive solution is 0.5-10%, and the mass ratio of adhesive to pore-forming agent in the first solution is 1 / 10-10 / 1; The first solution is dropped into the first catalyst slurry and dispersed evenly to obtain the outer catalyst layer slurry. In the outer catalyst layer slurry, the mass of the pore-forming agent is 10% to 20% of the total mass of the anti-CO platinum-based catalyst, binder and pore-forming agent. The preparation methods of the inner catalyst layer slurry include: The platinum-based catalyst was uniformly dispersed in a solvent to obtain a second catalyst slurry; Prepare an aqueous adhesive solution, add a pore-forming agent to the aqueous adhesive solution, and disperse it evenly to obtain a homogeneous and transparent second solution; the mass percentage of ionomer in the aqueous adhesive solution is 0.5~10%, and the mass ratio of adhesive to pore-forming agent in the second solution is 1 / 10~10 / 1; The second solution is added dropwise to the second catalyst slurry and dispersed evenly to obtain the inner catalyst layer slurry. In the inner catalyst layer slurry, the mass of the pore-forming agent is 5% to 10% of the total mass of the platinum-based catalyst, binder, and pore-forming agent. In the obtained outer catalyst layer, the mass percentage of the pore-forming agent is 10%~20%; in the obtained inner catalyst layer, the mass percentage of the pore-forming agent is 5%~10%. In both the outer catalyst layer and the inner catalyst layer, the mass percentage of the binder is 10%-40%, and the mass percentage of the binder in the outer catalyst layer is greater than that in the inner catalyst layer. The catalyst loading in both the outer and inner catalyst layers is 0.05~0.5 mg / cm³. 2 Furthermore, the catalyst loading in the outer catalyst layer is higher than that in the inner catalyst layer.

2. The method for preparing a fuel cell anode gas diffusion electrode with low CO mass transfer resistance according to claim 1, characterized in that, The conditions for heat treatment of impregnated paper, carbon cloth, carbon felt, titanium mesh or stainless steel mesh are 340~360℃ for 0.1~2 h.

3. The method for preparing a fuel cell anode gas diffusion electrode with low CO mass transfer resistance according to claim 1, characterized in that, The CO-resistant platinum-based catalyst in the outer catalyst layer slurry includes one or more of PtRu / C, PtSn / C, PtBi / C, or PtRh / C; The platinum-based catalyst in the inner catalyst layer slurry includes one or more of Pt black or Pt / C.

4. The method for preparing a fuel cell anode gas diffusion electrode with low CO mass transfer resistance according to claim 1, characterized in that, The outer catalyst layer slurry and the binder in the outer catalyst layer slurry include one or more of PTFE, PVDF, FEP, mPBI, ABPBI or PFA; The pore-forming agent in the outer catalyst layer slurry includes one or more of ammonium bicarbonate, ammonium oxalate, ammonium nitrate, or ammonium sulfate.

5. The method for preparing a fuel cell anode gas diffusion electrode with low CO mass transfer resistance according to claim 1, characterized in that, Methods for coating the diffusion layer surface with an external catalyst layer slurry include ultrasonic spraying, screen printing, or slit direct coating. After coating the diffusion layer surface with the external catalyst layer slurry, the resulting product is placed in a muffle furnace and calcined at 300℃~400℃ for 0.5h~2h to obtain the external catalyst layer. Methods for coating the outer catalyst layer surface with an inner catalyst layer slurry include ultrasonic spraying, screen printing, or slot direct coating. After coating the outer catalyst layer surface with the inner catalyst layer slurry, the resulting product is placed in a muffle furnace and calcined at 300℃~400℃ for 0.5h~2h to obtain the inner catalyst layer.

6. A fuel cell anode gas diffusion electrode with low CO mass transfer resistance, characterized in that, The anode gas diffusion electrode for a fuel cell with low CO mass transfer resistance is prepared by any one of claims 1-5, comprising a diffusion layer, an outer catalyst layer, and an inner catalyst layer. The porosity of the outer catalyst layer is 40%~50%, and the average pore size is 0.5~5μm; The porosity of the inner catalyst layer is 20%~30%, and the average pore size is 0.05~1μm.

Citation Information

Patent Citations

  • Catalytic layer with multi-layer structure of fuel cell and preparation method thereof

    CN108063267A

  • Anti-CO compound catalystic layer for proteon-exchange membrane fuel cell and its preparation

    CN1380712A